2020
DOI: 10.21037/tau.2019.08.14
|View full text |Cite
|
Sign up to set email alerts
|

The role of penectomy in penile cancer—evolving paradigms

Abstract: Penile cancer is a rare cancer, with the majority treated with penile preserving methods.There remains a role for partial and totally penectomy for advanced and more proximal penile cancers.Significant functional and psychological morbidity can ensue for patients undergoing surgical management.Recent studies and guidelines are changing the way Urologists approach surgical management of penile malignancies. Reductions in safe surgical margin recommendations from 2 cm to 3-5 mm provide surgeons with the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Both Romero et al [ 17 ] and Yu et al [ 11 ] reported an incision site which allowed a 2-cm margin of tumour-free tissue. However, more recent research suggests that safe surgical margins can be reduced from 2 cm to 3–5 mm, thus allowing greater preservation of penile lengths [ 43 ]. As such, patients undergoing partial penectomy may now expect to maintain greater penile lengths and sexual function than individuals historically undergoing this operation.…”
Section: Discussionmentioning
confidence: 99%
“…Both Romero et al [ 17 ] and Yu et al [ 11 ] reported an incision site which allowed a 2-cm margin of tumour-free tissue. However, more recent research suggests that safe surgical margins can be reduced from 2 cm to 3–5 mm, thus allowing greater preservation of penile lengths [ 43 ]. As such, patients undergoing partial penectomy may now expect to maintain greater penile lengths and sexual function than individuals historically undergoing this operation.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of penile cancer has not been explained clearly; however, there are conditions associated with penile cancer such as uncircumcised prepuce, chronic inflammatory conditions, and exposure to the human papilloma virus [4]. Poor hygiene, history of smoking, and history of phimosis were also found in 25% of patients with penile cancer [5]. Many cases of sclerofibroma reactions and advanced granulomas occurring after injection of liquid silicone were given to enlarge the penis [6].…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that the injection of liquid silicone to enlarge the penis can cause chronic inflammatory reactions. Silicone is a polymer that can be chemically injected into the soft tissue of the penis which forms into liquid silicone in the form of injection in a variety of cosmetic procedures [5]. Mainly done for tissue augmented, for example, lips, chin, breasts, buttocks, and penis.…”
Section: Discussionmentioning
confidence: 99%
“…Penectomy is still the “gold standard” for the treatment of primary tumors. It can be partial or total, depending on the extension of the lesion ( 6 , 7 ). In some patients, lymphadenectomy is essential for surgical management, although it presents risks of complications and has high morbidity.…”
Section: Introductionmentioning
confidence: 99%